Back Cover: The Fatty Acid Composition of Diacylglycerols Determines Local Signaling Patterns (Angew. Chem. Int. Ed. 24/2013). Issue 24 (31st May 2013) - Nadler, André; Reither, Gregor; Feng, Suihan; Stein, Frank; Reither, Sabine; Müller, Rainer; Schultz, Carsten
<x xml:space="preserve">Abstract</x> Photoactivatable or "caged" derivatives of signaling molecules are important tools for manipulating intracellular events with spatial and temporal resolution. In their Communication on page 6330 ff., C. Schultz and co‐workers demonstrate that regionally limited photoactivation simultaneously leads to a local protein kinase C and a global calcium response. Surprisingly, the orchestration of these effects seems to depend on the fatty acid composition of the released lipid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>